Mobile Apps Making a Socio-Economic Impact for Managing Power at Underprivileged Homes - Ashok Jhunjhunwala; Prabhjot Kaur; Anusha Ramachandran; Sai Ram Mannar; Mrinalini Ramakrishnan; Sree Hari Nagarajan (International Telecommunications Society (ITS), 2016)
The paper presents how connectivity feature integrated into a roof-top solar power system, Inverterless500, designed and developed to electrify off-grid and near off-grid homes in an energy efficient manner, is critical in optimum service delivery, especially for lower income homes. It makes such products not only suitable for different categories of homes, but also economically viable, offering a promising business solution. Monitoring and manageability are unique features that help in maintaining the solution at remote areas of installation where manual intervention is not routinely feasible. The paper the describes the technology and learnings gained from deployment of these systems that helped in improving the product and overall management process.
Keywords: 330; BLE; cloud; data monitoring portal; Energy efficiency; Inverterless; mobile app; monitoring; power management; Solar-DC